Combination of selective area sublimation of p-GaN and regrowth of AlGaN for the co-integration of enhancement mode and depletion mode high electron mobility transistors. (February 2022) - Ngo, Thi Huong; Comyn, Rémi; Chenot, Sébastien; Brault, Julien; Damilano, Benjamin; Vézian, Stéphane; Frayssinet, Eric; Cozette, Flavien; Defrance, Nicolas; Lecourt, François; Labat, Nathalie; Maher, Hassan; et al.
Highlights: Selective sublimation of p-GaN is developed to fabricate enhancement-mode HEMTs. AlGaN regrowth drastically reduces access resistances in enhancement-mode HEMTs. Sublimation and regrowth are combined to co-integrate E/D-mode GaN HEMTs. Abstract: We report on the fabrication of an enhancement mode p-GaN/AlN/GaN high electron mobility transistor with selective area sublimation under vacuum of the p-GaN cap layer. The GaN evaporation selectivity is demonstrated on the thin 2 nm AlN barrier layer. Furthermore, the regrowth of AlGaN is a major key to increase the maximum drain current in the transistors and enables the co-integration with depletion mode devices.